Economic Impact of Climate Smart Agriculture Practices: A Social Accounting Matrix (SAM) Analysis - Novitasari, Eka; Hartono, Djoni (Universitas Negeri Semarang, 2025)
This research was driven by climate change, which impacted the Indonesian economy. Climate Smart Agriculture (CSA) was selected to mitigate climate change while also potentially benefiting the economy. This study is to explore the economic impacts of CSA practices on rice, coffee, maize and sugarcane. The SAM approach was selected due to its ability in providing comprehensive and in-depth analysis, emphassing the significance of employment, household, and social institutions in the economy. Additionally, it incorporates transactions and transfers between institutions that are relevant to income distribution (Morales, 2024). Nine scenarios with an implementation level of 18 and a successful rate of 80%, were chosen to demonstrate the potential for increasing sectoral income, labour income, household income, value added and employment. The findings indicate that CSA has the potential to present positive impact on the economy, thus the government is encouraged to implement CSA practices in various regions of Indonesia.